Pengembangan Game Edukasi Spinning Wheel Untuk Meningkatkan Perkembangan Bahasa Anak Kelompok B Di PAUD Semai Harapan Bangsa Mataram - Nasya Ulfa; Gunawan Gunawan; Baik Nilawati Astini; Fahruddin Fahruddin (Indonesian Journal of Elementary and Childhood Education, 2024)
This study aims to develop an educational game "Spinning Wheel" that is effective in improving the language development of group B children at PAUD Semai Harapan Bangsa Mataram. Language development is an important aspect in the growth and development of early childhood, and the use of interactive game media is believed to be an interesting and effective approach. The use of games in the learning process to improve children's language development shows several aspects that have increased. One of them is the ability to tell stories, where children will tell what they see and what they feel after using the game. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the study were 8 children in group B who were selected randomly. The research instruments used were language ability tests, observation sheets, and child response questionnaires. The results of the study showed that the educational game "Spinning Wheel" had been successfully developed and validated by media experts and material experts. Field trials showed a significant increase in children's language skills after using this game. Children also showed high enthusiasm and interest while playing. The children's response questionnaire revealed that they felt happy and motivated to learn through the "Spinning Wheel" game. Based on the results of the study, it can be concluded that the educational game "Spinning Wheel" is an effective learning media to improve the language development of children in group B. This game can be used as an alternative to fun and interactive learning activities at PAUD Semai Harapan Bangsa Mataram.